Effectiveness and Contribution Analysis of Regional Taxes to the Growth of Local Own-source Revenue in Kediri During and Post-COVID-19 Pandemic - Theresa Grace Abdi Tobong; Anna Isrowiyah; Putri Ayu Berlianingtyas (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2025)
This study aims to evaluate the effectiveness and contribution of hotel, restaurant, and entertainment taxes in supporting the growth of Kediri’s regional original revenue during and in the period following the COVID-19 pandemic. The data used are secondary data from 2020 to 2024. This study applies a descriptive quantitative method, with data collected through interviews and documentation. The data were sourced from the Regional Revenue, Financial, and Asset Management Agency of Kediri. This method was used to measure the effectiveness of regional tax realization against the target and the contribution of realized hotel tax revenue, restaurant tax, and entertainment tax to local revenue. The data in this study are the target and realized hotel tax revenue, restaurant tax, entertainment tax, and local revenue. The findings of this study reveal that during the COVID-19 pandemic period (2020–2021), hotel and restaurant tax revenues demonstrated a very high level of effectiveness, whereas entertainment tax revenue was considered moderately effective. In the post-COVID-19 pandemic in 2022, hotel taxes and restaurant taxes decreased while entertainment tax increased. In 2023, hotel taxes and restaurant taxes increased while entertainment tax decreased. In 2024, the effectiveness rate increased across various sectors. Hotel and restaurant taxes were highly effective, apart from entertainment taxes, which were moderately effective. The contribution of hotel, restaurant, and entertainment taxes to the growth of Kediri's regional original income during and after the COVID-19 pandemic was very low.